Lost in Transmission? Stock Market Impacts of the 2006 European Gas Crisis - Ulrich Oberndorfer; Dirk Ulbricht; Janina Ketterer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2007)
Around the turn of the year 2005/2006, the Russian freezing of natural gas exports to the Ukraine led to a European gas crisis. Using event study techniques, we first investigate whether the Russian suspension of gas deliveries, the announcement of this suspension as well as its withdrawal had an effect on unsystematic volatility of European energy stocks. Second, we measure event effects on stock returns, taking volatility (GARCH effects) and especially possible firm-specific, event-induced volatility into account. We get at a first glance counterintuitive results suggesting that the definite announcement of the crisis and therefore a rise of Western Europes energy risk tended to increase market expectations with respect to energy-related firms. In contrast, market uncertainty increased the day when Russia reopened its valves. One reason for these findings could be windfall profits of energy-related companies due to increasing resource and electricity prices. The existence of event-induced volatility at a between-firm level confirms the choice of our flexible abnormal returns methodology.
Keywords: G14; Q41; Q43; 330; Energy security; event study; gas crisis